Sorption Characteristics of Mixed Molecules of Glutaraldehyde from Water on Mesoporous Acid-Amine Modified Low-Cost Activated Carbon: Mechanism, Isotherm, and Kinetics - Mukosha Lloyd; Onyango S. Maurice; Ochieng Aoyi; Taile Y. Leswifi (Journal of Chemistry)
The environmental discharge of inefficiently treated waste solutions of the strong biocide glutaraldehyde (GA) from hospitals has potential toxic impact on aquatic organisms. The adsorption characteristics of mixed polarized monomeric and polymeric molecules of GA from water on mesoporous acid-amine modified low-cost activated carbon (AC) were investigated. It was found that the adsorption strongly depended on pH and surface chemistry. In acidic pH, the adsorption mechanism was elaborated to involve chemical sorption of mainly hydroxyl GA monomeric molecules on acidic surface groups, while in alkaline pH, the adsorption was elaborated to involve both chemical and physical sorption of GA polymeric forms having mixed functional groups (aldehyde, carboxyl, and hydroxyl) on acidic and amine surface groups. The optimum pH of adsorption was about 12 with significant contribution by cooperative adsorption, elucidated in terms of hydrogen bonding and aldol condensation. Freundlich and Dubinin-Radushkevich models were fitted to isotherm data. The adsorption kinetics was dependent on initial concentration and temperature and described by the Elovich model. The adsorption was endothermic, while the intraparticle diffusion model suggested significant contribution by film diffusion. The developed low-cost AC could be used to supplement the GA alkaline deactivation process for efficient removal of residual GA aquatic toxicity.